Low-carbon magnesia carbon brick for permanent layer of converter as well as preparation method and application of low-carbon magnesia carbon brick
By introducing low-quality graphite, high-temperature asphalt powder and phenolic resin into the refractory materials for the permanent layer of the converter, low-carbon magnesium carbon bricks were prepared, which solved the problem of insufficient thermal shock stability and hydration resistance of existing refractory materials under emergency cold and heat conditions, and achieved higher thermal shock stability, hydration resistance and thermal insulation effects, extending the furnace lining life and improving the safety factor.
Patent Information
- Application Number
- CN202510075746.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
The refractory materials used for the permanent layer of the existing converter have poor thermal shock stability and hydration resistance under the conditions of emergency and cold heat, which can easily lead to cracks and peeling, thereby shortening the furnace lining life.
Low-carbon magnesium carbon bricks are used to improve thermal shock resistance, reduce thermal conductivity, enhance corrosion resistance, and prevent hydration in a short time by introducing low-quality graphite, high-temperature asphalt powder and phenolic resin.
It significantly improves the thermal shock stability and hydration resistance of low-carbon magnesium carbon bricks, enhances the thermal insulation effect and resistance to slag invasion and water corrosion of steel, extends the service life of the furnace lining and improves the safety factor.
Smart Images

Figure BDA0005247027700000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a low-carbon magnesia-carbon brick for a permanent layer of a converter, and a preparation method and application thereof. Background Art
[0002] The converter body is composed of a steel structure furnace shell and an inner lining of refractory materials. The inner lining of refractory materials is generally divided into three parts: a thermal insulation layer, a permanent layer, and a working layer. The permanent layer plays the role of heat preservation, heat insulation, and improving the safety factor. At present, fired magnesia bricks are generally used as the refractory material for the permanent layer.
[0003] However, the process of firing magnesia bricks is complicated and requires high-temperature firing. Its production cost is relatively high. In addition, due to its poor thermal shock stability, it is easy to crack and peel off under the conditions of rapid cooling and heating. The water-cooling box at the converter mouth operates at high temperature and inevitably leaks frequently. The fired magnesia bricks have poor resistance to hydration, which reduces their strength, causing local or even large-scale permanent lining shedding, shortening the life of the furnace lining.
[0004] Therefore, how to provide a refractory material for the permanent layer of a converter that has the characteristics of thermal insulation, heat insulation, high thermal shock resistance, not easy to hydrate in a short time, and prevents steel leakage when the working layer is partially melted or the entire layer is too thin is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a low-carbon magnesium carbon brick for the permanent layer of a converter and a preparation method thereof. The low-carbon magnesium carbon brick has a low carbon content. By introducing a low amount of graphite and high-temperature asphalt powder, the thermal shock resistance of the low-carbon magnesium carbon brick is improved, the thermal conductivity is reduced, the corrosion resistance is improved, it is not easy to hydrate in a short time, and it has the purpose of heat preservation, heat insulation and improved safety factor.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A low-carbon magnesia-carbon brick for a permanent layer of a converter comprises the following raw materials in parts by weight:
[0008] 72-75 parts of fused magnesia particles, 22-25 parts of fused magnesia fine powder, 1-2 parts of flake graphite, 0.5-1 parts of resin powder, 0.5 parts of high-temperature asphalt powder and 2-3 parts of phenolic resin.
[0009] Sintered magnesia bricks have excellent high temperature resistance and strong resistance to alkaline slag erosion. They can maintain stable physical and chemical properties under high temperature environment and have good thermal insulation effect. However, sintered magnesia bricks have poor thermal shock stability and hydration resistance. They are prone to cracking and peeling under conditions of rapid cooling and heating, which can easily shorten the life of the furnace lining. Traditional magnesia carbon bricks have replaced sintered magnesia bricks, but due to their high carbon content and strong heat conduction ability, they can easily cause the furnace wall to turn red in the later stage of the use of the furnace lining, resulting in poor thermal insulation effect and easy to cause steel penetration accidents. The low-carbon magnesia carbon bricks for the permanent layer of the converter of the present invention introduce a small amount of graphite to reduce the carbon content, thereby reducing the thermal conductivity, improving the thermal shock stability and hydration resistance, significantly improving the thermal insulation effect, and having stronger resistance to slag invasion and molten steel erosion, thereby effectively protecting the stability of the permanent lining of the converter and improving the safety factor.
[0010] Preferably, the particle size of the fused magnesia particles is 5-3mm, 3-1mm, 1-0mm, and the magnesium oxide content is ≥96wt%;
[0011] Wherein, the mass ratio of the 5-3mm, 3-1mm and 1-0mm fused magnesia particles is 20-23:25-26:20-23.
[0012] Preferably, the particle size of the fused magnesia fine powder is 180-200 mesh, and the magnesium oxide content is ≥96wt%.
[0013] Preferably, the particle size of the flake graphite is 100-200 mesh, and the C content of the graphite is ≥93wt%.
[0014] Preferably, the high-temperature asphalt powder has a residual carbon content of ≥50wt%, an ash content of ≤1.5wt%, and a volatile matter of ≤45wt%.
[0015] Preferably, the chemical weight percentage and indexes of the phenolic resin are: solid content ≥80wt%, residual carbon ≥46wt%, and moisture ≤3.0wt%.
[0016] Preferably, the high-temperature asphalt powder is in the form of solid powder.
[0017] According to the above-mentioned method for preparing low-carbon magnesia-carbon bricks for the permanent layer of a converter, it is characterized by comprising the following steps:
[0018] (1) Weigh the following raw materials by weight: 72-75 parts of fused magnesia particles, 22-25 parts of fused magnesia fine powder, 1-2 parts of flake graphite, 0.5-1 parts of resin powder, 0.5 parts of high-temperature asphalt powder and 2-3 parts of phenolic resin, and set aside;
[0019] (2) mixing the resin powder and the high-temperature asphalt powder uniformly to obtain a premixed powder for later use;
[0020] (3) After the fused magnesia particles are dry-mixed evenly, 1 / 2-1 / 3 of the mass of the phenolic resin is added and mixed evenly, the graphite and the remaining phenolic resin are added and mixed evenly, and then the fused magnesia fine powder and the premixed powder are added in sequence and mixed evenly, and then the materials are trapped and pressed to obtain a brick blank, and the brick blank is heat-treated to obtain a low-carbon magnesia-carbon brick for the permanent layer of the converter.
[0021] Preferably, the dry mixing time in step (3) is 3-5 min;
[0022] The mixing time of the fused magnesia particles and the phenolic resin is 5-8 minutes;
[0023] The mixing time of the graphite and the remaining phenolic resin is 5-10 minutes;
[0024] The mixing time of the fused magnesia fine powder is 10-30min;
[0025] The mixing time of the premixed powder is 3-5 minutes.
[0026] Preferably, the time of trapping the material in step (3) is 4-6 hours, the temperature is 10-15° C., and the humidity is 30-40%;
[0027] The heat treatment condition is 140°C-180°C for 8-10 hours.
[0028] The use of the low-carbon magnesia-carbon brick as described above or the low-carbon magnesia-carbon brick obtained by the above-described preparation method in the preparation of the permanent layer of the converter.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) Compared with ordinary fired magnesia bricks, the low-carbon magnesia carbon bricks of the present invention are not easy to hydrate in a short time, have stronger resistance to slag erosion, and have higher thermal shock stability. They are used in the permanent layer of the molten pool at the bottom of the furnace to hold steel. If steel leakage occurs, the safety factor is higher;
[0031] (2) The low-carbon magnesium carbon brick of the present invention introduces a low amount of graphite, which can improve thermal shock stability, reduce thermal conductivity, and have anti-oxidation performance. At the same time, it also has high slag erosion resistance, high oxidation resistance, and high thermal shock stability, meeting the smelting needs of steel mills under rapid cooling and heating conditions;
[0032] (3) Adding resin powder to the raw materials of the low-carbon magnesium carbon brick of the present invention is beneficial to increasing the plasticity of the mixed mud and helping to improve the brick forming strength;
[0033] (4) High-temperature asphalt powder is added to the raw materials of the low-carbon magnesium carbon bricks of the present invention. The asphalt melts at high temperature and fills the gaps between the materials, thereby reducing the porosity of the magnesium carbon bricks and increasing the overall strength and structural stability of the materials. In addition, the asphalt's anti-oxidation and anti-high-temperature deformation capabilities can inhibit the oxidation and creep of the magnesium carbon bricks in a high-temperature environment, thereby maintaining the stability of their shape and size.
[0034] (5) The preparation method of the present invention has readily available raw materials, simple process steps, and low requirements on production equipment, and is suitable for mass production. DETAILED DESCRIPTION
[0035] The following describes embodiments of the present invention, which are exemplary and intended to be used to explain the present invention, but are not to be construed as limiting the present invention.
[0036] Raw materials:
[0037] The magnesium oxide content of fused magnesia particles is ≥96wt%;
[0038] The particle size of the fused magnesia fine powder is 180 mesh, and the magnesium oxide content is ≥96wt%;
[0039] The particle size of flake graphite is 100 mesh, and the C content of graphite is ≥93wt%;
[0040] The residual carbon content of high temperature asphalt powder is ≥50wt%, ash content is ≤1.5wt%, and volatile matter is ≤45wt%;
[0041] The chemical weight percentage and indexes of the phenolic resin are: solid content ≥ 80wt%, residual carbon ≥ 46wt%, moisture ≤ 3.0wt%;
[0042] High temperature asphalt powder is in solid powder form.
[0043] Example 1
[0044] The present invention provides a low-carbon magnesium carbon brick for a permanent layer of a converter, and the preparation method specifically comprises the following steps:
[0045] (1) Weigh raw materials: by weight, 23 parts of 3-5mm fused magnesia particles, 26 parts of 3-1mm fused magnesia particles, 23 parts of 1-0mm fused magnesia particles, 23 parts of fused magnesia fine powder, 1 part of flake graphite, 0.5 part of resin powder, 0.5 part of high-temperature asphalt powder, and 3 parts of phenolic resin, for standby use;
[0046] (2) Mix the resin powder and high-temperature asphalt powder for 20 minutes. Mix them evenly to obtain premixed powder for later use.
[0047] (3) The weighed fused magnesia granular aggregate was dry-mixed in a high-speed mixer (rotation speed: 740 rpm) for 3 min, and then about 1 / 2 of the total amount of phenolic resin was added and mixed for 5 min, and graphite and the remaining phenolic resin were added and mixed for 5 min, requiring that the graphite was evenly wrapped on the wetted aggregate, and finally fused magnesia fine powder was added and mixed for 10 min, and then the premixed powder was added and mixed for 3 min to obtain a mud material;
[0048] (4) Molding: The mixed mud is loaded into a hopper and trapped for 4 hours at a temperature of 10-15°C and a humidity of 30-40%. It is then pressed into a 230mm long * 115mm wide * 65mm thick brick shape under the pressure of a 1250KN electric screw press. The obtained brick is heat treated at 140-180°C and dried for 8 hours to obtain a low-carbon magnesium carbon brick.
[0049] Example 2
[0050] The present invention provides a low-carbon magnesium carbon brick for a permanent layer of a converter, and the preparation method specifically comprises the following steps:
[0051] (1) Weigh raw materials: by weight, 23 parts of 3-5mm fused magnesia particles, 26 parts of 3-1mm fused magnesia particles, 23 parts of 1-0mm fused magnesia particles, 22 parts of fused magnesia fine powder, 2 parts of flake graphite, 0.5 part of resin powder, 0.5 part of high-temperature asphalt powder, and 3 parts of phenolic resin, for standby use;
[0052] (2) Mix the resin powder and high-temperature asphalt powder for 30 minutes until they are evenly mixed to obtain a premixed powder for later use.
[0053] (3) The weighed fused magnesia granular aggregate was dry-mixed in a high-speed mixer (rotation speed: 740 rpm) for 5 min, and then about 1 / 2 of the total amount of phenolic resin was added and mixed for 5 min. Graphite and the remaining phenolic resin were added and mixed for 10 min. The graphite was required to be evenly wrapped on the wetted aggregate. Finally, fused magnesia fine powder was added and mixed for 20 min, and then the premixed powder was added and mixed for 5 min to obtain a mud material;
[0054] (4) Molding: The mixed mud is loaded into a hopper and trapped for 6 hours at a temperature of 10-15°C and a humidity of 30-40%. It is then pressed into a 230mm long * 115mm wide * 65mm thick brick shape under the pressure of a 1250KN electric screw press. The obtained brick is heat treated at 140-180°C and dried for 10 hours to obtain a low-carbon magnesium carbon brick.
[0055] Example 3
[0056] The present invention provides a low-carbon magnesium carbon brick for a permanent layer of a converter, and the preparation method specifically comprises the following steps:
[0057] (1) Weigh raw materials: by weight, 23 parts of 3-5mm fused magnesia particles, 26 parts of 3-1mm fused magnesia particles, 23 parts of 1-0mm fused magnesia particles, 22 parts of fused magnesia fine powder, 1.5 parts of flake graphite, 1 part of resin powder, 0.5 part of high-temperature asphalt powder, and 3 parts of phenolic resin, for standby use;
[0058] (2) Mix the resin powder and high-temperature asphalt powder for 20 minutes to obtain a premixed powder for later use.
[0059] (3) The weighed fused magnesia granular aggregate was dry-mixed in a high-speed mixer (rotation speed: 740 rpm) for 5 min, and then about 1 / 2 of the total amount of phenolic resin was added and mixed for another 5 min, and graphite and the remaining phenolic resin were added and mixed for 5 min, requiring that the graphite was evenly wrapped on the wetted aggregate, and finally fused magnesia fine powder was added and mixed for 30 min, and then the premixed powder was added and mixed for 5 min to obtain a mud material;
[0060] (4) Molding: The mixed mud is loaded into a hopper and trapped for 6 hours at a temperature of 10-15°C and a humidity of 30-40%. It is then pressed into a 230mm long * 115mm wide * 65mm thick brick shape under the pressure of a 1250KN electric screw press. The obtained brick is heat treated at 140-180°C and dried for 10 hours to obtain a low-carbon magnesium carbon brick.
[0061] Comparative Example 1
[0062] A magnesia carbon brick is provided, and the preparation method specifically comprises the following steps:
[0063] (1) Weigh raw materials: by weight, 23 parts of 3-5mm fused magnesia particles, 26 parts of 3-1mm fused magnesia particles, 23 parts of 1-0mm fused magnesia particles, 23 parts of fused magnesia fine powder, 0.5 part of flake graphite, 0.5 part of resin powder, 1 part of high-temperature asphalt powder, and 3 parts of phenolic resin, for standby use;
[0064] (2) Mix the resin powder and high-temperature asphalt powder for 20 minutes to obtain a premixed powder for later use.
[0065] (3) The weighed fused magnesia granular aggregate was dry-mixed in a high-speed mixer (rotation speed: 740 rpm) for 5 min, and then about 1 / 2 of the total amount of phenolic resin was added and mixed for another 5 min, and graphite and the remaining phenolic resin were added and mixed for 5 min, requiring that the graphite was evenly wrapped on the wetted aggregate, and finally fused magnesia fine powder was added and mixed for 30 min, and then the premixed powder was added and mixed for 5 min to obtain a mud material;
[0066] (4) Molding: The mixed mud is loaded into a hopper and trapped for 6 hours at a temperature of 10-15°C and a humidity of 30-40%. It is then pressed into a 230mm long * 115mm wide * 65mm thick brick shape under the pressure of a 1250KN electric screw press. The obtained brick is heat treated at 140-180°C and dried for 10 hours to obtain a low-carbon magnesium carbon brick.
[0067] Comparative Example 2
[0068] A magnesia carbon brick is provided, and the preparation method specifically comprises the following steps:
[0069] (1) Weigh raw materials: by weight, 23 parts of 3-5mm fused magnesia particles, 26 parts of 3-1mm fused magnesia particles, 23 parts of 1-0mm fused magnesia particles, 23 parts of fused magnesia fine powder, 0.5 part of flake graphite, 0.5 part of resin powder, 0.5 part of high-temperature asphalt powder, and 3 parts of phenolic resin for standby use;
[0070] (2) Mix the resin powder and high-temperature asphalt powder for 20 minutes to obtain a premixed powder for later use.
[0071] (3) The weighed fused magnesia granular aggregate was dry-mixed in a high-speed mixer (rotation speed: 740 rpm) for 5 min, and then about 1 / 2 of the total amount of phenolic resin was added and mixed for another 5 min, and graphite and the remaining phenolic resin were added and mixed for 5 min, requiring that the graphite was evenly wrapped on the wetted aggregate, and finally fused magnesia fine powder was added and mixed for 30 min, and then the premixed powder was added and mixed for 5 min to obtain a mud material;
[0072] (4) Molding: The mixed mud is loaded into a hopper and trapped for 6 hours at a temperature of 10-15°C and a humidity of 30-40%. It is then pressed into a 230mm long * 115mm wide * 65mm thick brick shape under the pressure of a 1250KN electric screw press. The obtained brick is heat treated at 140-180°C and dried for 10 hours to obtain a low-carbon magnesium carbon brick.
[0073] Comparative Example 3
[0074] A magnesia carbon brick is provided, and the preparation method specifically comprises the following steps:
[0075] (1) Weigh raw materials: by weight, 23 parts of 3-5mm fused magnesia particles, 26 parts of 3-1mm fused magnesia particles, 23 parts of 1-0mm fused magnesia particles, 23 parts of fused magnesia fine powder, 1 part of flake graphite, 0.5 part of resin powder, 1 part of high-temperature asphalt powder, and 3 parts of phenolic resin, for standby use;
[0076] (2) Mix the resin powder and high-temperature asphalt powder for 20 minutes to obtain a premixed powder for later use.
[0077] (3) The weighed fused magnesia granular aggregate was dry-mixed in a high-speed mixer (rotation speed: 740 rpm) for 5 min, and then about 1 / 2 of the total amount of phenolic resin was added and mixed for another 5 min, and graphite and the remaining phenolic resin were added and mixed for 5 min, requiring that the graphite was evenly wrapped on the wetted aggregate, and finally fused magnesia fine powder was added and mixed for 30 min, and then the premixed powder was added and mixed for 5 min to obtain a mud material;
[0078] (4) Molding: The mixed mud is loaded into a hopper and trapped for 6 hours at a temperature of 10-15°C and a humidity of 30-40%. It is then pressed into a 230mm long * 115mm wide * 65mm thick brick shape under the pressure of a 1250KN electric screw press. The obtained brick is heat treated at 140-180°C and dried for 10 hours to obtain a low-carbon magnesium carbon brick.
[0079] The low carbon magnesia carbon bricks of Examples 1-3, conventional fired magnesia bricks (with magnesia as the main raw material, alkaline refractory materials fired at high temperature, without flake graphite, resin powder, high temperature asphalt powder) and comparative examples 1-3 magnesia carbon bricks were tested respectively, and the results are shown in Table 1 below;
[0080] Table 1 Test results of low carbon magnesia carbon bricks of Examples 1-3, conventional fired magnesia bricks and magnesia carbon bricks of Comparative Examples 1-3
[0081]
[0082] Through the low-carbon magnesia carbon bricks prepared in Example 1, Example 2, and Example 3, as well as the detection of various data of conventional fired magnesia bricks, it can be known that the low-carbon magnesia carbon bricks for the permanent layer of the converter provided by the present invention reduce the use of graphite, and adopt a special preparation method to prepare a low-carbon magnesia carbon brick with excellent heat insulation, thermal insulation, and slag invasion resistance, which has excellent strength and good thermal shock stability.
[0083] At the same time, it can be seen from the table that the physical and chemical testing indicators in the embodiment are good. After being used in a 210-ton converter in a steel plant and built in the permanent layer of the furnace bottom and the molten pool where steel is stored, the thermal insulation, heat insulation, and thermal shock stability have been significantly improved, and the safety factor has been significantly improved.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low carbon magnesia carbon brick for permanent layer of converter, characterized in that: Including the following raw materials by weight: 72-75 parts of fused magnesia particles, 22-25 parts of fused magnesia fine powder, 1-2 parts of flake graphite, 0.5-1 parts of resin powder, 0.5 parts of high-temperature asphalt powder and 2-3 parts of phenolic resin.
2. According to claim 1, a low-carbon magnesium-carbon brick for a permanent layer of a converter is characterized in that: The particle size of the fused magnesia particles is 5-3mm, 3-1mm, 1-0mm, and the magnesium oxide content is ≥96wt%; Wherein, the mass ratio of the 5-3mm, 3-1mm and 1-0mm fused magnesia particles is 20-23:25-26:20-23.
3. The low carbon magnesia carbon brick for permanent layer of converter according to claim 1, characterized in that: The particle size of the fused magnesia fine powder is 180-200 meshes, and the magnesium oxide content is ≥96wt%.
4. The low carbon magnesia carbon brick for permanent layer of converter according to claim 1, characterized in that: The particle size of the flake graphite is 100-200 meshes, and the C content of the graphite is ≥93wt%.
5. The low carbon magnesia carbon brick for permanent layer of converter according to claim 1, characterized in that: The high-temperature asphalt powder has a residual carbon content of ≥50wt%, an ash content of ≤1.5wt%, and a volatile matter of ≤45wt%.
6. The low carbon magnesia carbon brick for permanent layer of converter according to claim 1, characterized in that: The chemical weight percentage and indexes of the phenolic resin are: solid content ≥80wt%, residual carbon ≥46wt%, and moisture ≤3.0wt%.
7. The method for preparing a low-carbon magnesia-carbon brick for a permanent layer of a converter according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weigh the following raw materials by weight: 72-75 parts of fused magnesia particles, 22-25 parts of fused magnesia fine powder, 1-2 parts of flake graphite, 0.5-1 parts of resin powder, 0.5 parts of high-temperature asphalt powder and 2-3 parts of phenolic resin, and set aside; (2) mixing the resin powder and the high-temperature asphalt powder uniformly to obtain a premixed powder for later use; (3) After the fused magnesia particles are dry-mixed uniformly, 1 / 2-1 / 3 of the mass of the phenolic resin is added and mixed uniformly, the graphite and the remaining phenolic resin are added and mixed uniformly, and then the fused magnesia fine powder and the premixed powder are added in sequence and mixed uniformly, and then the materials are trapped and pressed to obtain a brick blank, and the brick blank is heat-treated to obtain a low-carbon magnesia-carbon brick for the permanent layer of the converter.
8. The method for preparing low-carbon magnesia carbon bricks for permanent layer of converter according to claim 7, characterized in that: The dry mixing time in step (3) is 3-5 minutes; The mixing time of the fused magnesia particles and the phenolic resin is 5-8 minutes; The mixing time of the graphite and the remaining phenolic resin is 5-10 minutes; The mixing time of the fused magnesia fine powder is 10-30min; The mixing time of the premixed powder is 3-5 minutes.
9. The method for preparing low-carbon magnesia carbon bricks for permanent layer of converter according to claim 7, characterized in that: The time of trapping the material in step (3) is 4-6 hours, the temperature is 10-15° C., and the humidity is 30-40%; The heat treatment condition is 140°C-180°C for 8-10 hours.
10. Use of the low-carbon magnesia-carbon brick according to any one of claims 1 to 6 or the low-carbon magnesia-carbon brick obtained by the preparation method according to any one of claims 7 to 9 in preparing a permanent layer of a converter.
Citation Information
Patent Citations
Low-carbon magnesium carbon brick and preparation thereof
CN101343188A
Ladle slag line magnesia carbon brick and preparation method thereof
CN102898156A
Low carbon magnesium carbon brick for ladles, and preparation method thereof
CN107285744A
High-temperature treated magnesia carbon brick for RH dip pipe and circulating pipe and preparation method thereof
CN112897992A
High-performance magnesia carbon brick for trunnion and slag line part of converter and production process of high-performance magnesia carbon brick
CN116199500A